2000
DOI: 10.1097/00001756-200008210-00035
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural sensitization to cocaine is dissociated from changes in striatal NMDA receptor levels

Abstract: Changes in glutamate transmission and alterations in glutamate receptor expression produced by the repeated administration of psychomotor stimulant drugs are considered an important neuroadaptation underlying the development and expression of behavioural and neurochemical sensitization to stimulant drugs. Two parallel experiments investigated the effects of repeated cocaine administration (five, once daily injections of 15 mg/kg, i.p.; 2 weeks withdrawal) on the expression of behavioural sensitization in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Our findings of decreased binding of NMDA receptors in the mPFC of the Coc1h group are consistent with those of Bhargava & Kumar (1999) showing decreased binding of NMDA receptors in the cortex of mice exhibiting behavioral sensitization to cocaine, immediately after the last cocaine challenge. Szumlinski et al, (2000) and Itzhak & Martin (2000) found no change in NMDA binding in the striatum of rats or the striatum and frontal cortex of mice, respectively, 14 or 10 days after the cessation of sensitization inducing regimen. This is consistent with the lack of change in NMDA binding we observed after 14 days of withdrawal in the striatum and mPFC of Coc1h rats.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings of decreased binding of NMDA receptors in the mPFC of the Coc1h group are consistent with those of Bhargava & Kumar (1999) showing decreased binding of NMDA receptors in the cortex of mice exhibiting behavioral sensitization to cocaine, immediately after the last cocaine challenge. Szumlinski et al, (2000) and Itzhak & Martin (2000) found no change in NMDA binding in the striatum of rats or the striatum and frontal cortex of mice, respectively, 14 or 10 days after the cessation of sensitization inducing regimen. This is consistent with the lack of change in NMDA binding we observed after 14 days of withdrawal in the striatum and mPFC of Coc1h rats.…”
Section: Discussionmentioning
confidence: 93%
“…• an upregulation of NMDA receptor binding in the regions such as the cortex, striatum, amygdala and hippocampus has been reported following repeated cocaine exposure [124][125][126] but see [127] • a decrease in NR1 and/or NR2B/2C expression in regions such as globus pallidus, subiculum, striatum, and cerebellum [98,105] • an up-regulation of NR1 and a down-regulation of GluR2-7 and KA2 expression in cerebral cortex [97,108,128] • increased phosphorylation of GluR1 in the prefrontal cortex [115] • an increase in mGluR5 expression in the hippocampus [129] • bidirectional alterations in the expression of NMDA and AMPA receptor subunit expression in the amygdala [130,131] A role for glutamatergic transmission in the rewarding and reinforcing effects of cocaine has been clearly demonstrated by pharmacological studies utilizing iGluR antagonists. Systemic administration of NMDA antagonists attenuate cocaine reinforcement [132][133][134][135] and the acquisition and/or expression of a cocaine CPP [136,137].…”
Section: Glutamate and Cocainementioning
confidence: 99%
“…Results of the binding studies are similarly contradictory: In one report, 3 H-CGP39653 binding increases after 3 days of non-contingent cocaine and 10 days of withdrawal, but does not change after 10 days of non-contingent cocaine and 10 days of withdrawal (Itzhak and Martin, 2000). 3 H-MK801 binding to the NMD ARs does not change after 5 days of non-contingent cocaine and 14 days of withdrawal (Szumlinski et al, 2000). Only a handful of reports examine the effects of self-administered cocaine on NMDAR expression in dorsal striatum with one finding no effects of self-administration on 3 H-MK801 binding (Ben-Shahar et al, 2007) and one reporting an increase in GluN1 expression immediately following 21 days of cocaine self-administration (Crespo et al, 2002).…”
Section: Cocaine Effects On Nmdar Expressionmentioning
confidence: 99%